Wrongful Convictions in Japan: Causes, Challenges, and Preventive Measures - Nishi, Yoshiyuki (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2025)
This article examines the causes and prevention of wrongful convictions in Japan. The criminal justice system heavily relies on interrogations, reinforced by systemic flaws. With an exceptionally high conviction rate, judges’ role in determining guilt is largely limited, making prosecutors the key decision-makers. Once indicted, innocent individuals face severe disadvantages. These structural issues contribute to wrongful convictions, particularly through false confessions and accomplice false testimony. Psychological factors such as confirmation bias, recognized globally as a major cause of wrongful convictions, also play a role in Japan. This highlights the universality of wrongful conviction risks and underscores the need for international collaboration. Since transitioning away from interrogation-dependent investigations is difficult, developing an alternative investigative model is essential, further emphasizing the importance of global research. For prevention, Japan has traditionally relied on judges refining fact-finding through evidentiary evaluation and the Cautionary Principle. While this helps ensure logical reasoning, it carries risks, as the principle itself may have flaws and is not always applied consistently. To address the recurring causes of wrongful convictions, a new approach has been proposed in Japan, integrating risk management principles. By systematically analyzing past wrongful conviction cases, this method seeks to prevent future errors. The principle of “learning about and from wrongful convictions” is emerging as a critical theme in global wrongful conviction research.